Electronic modulation of NiO by constructing an amorphous/crystalline heterophase to improve photocatalytic hydrogen evolution. Issue 36 (1st September 2022) - Cai, Linke; Yan, Bo; Xue, Qian; Li, Jiling; Liu, Pu; Qi, Xueqiang; Yang, Guowei
Abstract : An interface between amorphous and crystalline phases plays an important role in improving the photocatalytic performance due to the optimization of both the conductivity and the reaction activity of active sites of cocatalysts simultaneously. Abstract : An interface between amorphous and crystalline phases plays an important role in improving the photocatalytic performance due to the optimization of both the conductivity and the reaction activity of active sites of cocatalysts simultaneously. In this contribution, NiO including many amorphous–crystalline interfaces is prepared by a process of laser ablation in liquids, which is subsequently loaded on graphitic-C3 N4 (CN). It is found that a maximum photocatalytic hydrogen evolution rate of 2315.75 μmol g −1 h −1 is achieved by the NiO4 –CN composite with a favorable stability. The NiO with an amorphous/crystalline heterostructure serves as an effective cocatalyst for providing ample active sites with appropriate adsorption ability and promoting charge separation. A reduced Δ G H* is calculated by density functional theory, which results from the electronic modulation at the amorphous/crystalline interface. Meanwhile, the conductivity can be enhanced by the embedded crystalline phase in amorphous NiO, which promotes electron transfer and the separation of photoinduced carriers. These results suggest that the critical role of amorphous–crystalline interfaces in the promotion of the cocatalytic activity provides a promising strategy to exploit efficient cocatalysts as a supplement to conventional strategies.